Dynamic Associations of Negative Mood and Smoking across the Development of Smoking in Adolescence - Weinstein, Sally M. (2013)
OBJECTIVE: Self-medication models of smoking posit that the emotional benefits of smoking reinforce and maintain cigarette use, yet research demonstrates both positive and adverse affective consequences of smoking. The current study examined longitudinal changes in adolescent mood variability and overall negative mood at various stages of smoking behavior to inform understanding of the etiology of adolescent smoking. METHOD: Participants included 461 adolescents (mean age = 15.67 years, SD = 0.61; 55% girls; 56.8% white) drawn from a longitudinal study of adolescent smoking. Youth provided data on smoking behavior at baseline and a 15-month follow-up wave. Ecological momentary assessments (EMA) were used to measure overall levels of negative mood as well as within-person mood fluctuations (i.e., negative mood variability) at each wave. RESULTS: Findings revealed that smoking-mood relations vary across different stages of smoking behavior. Youth who rapidly escalated in their smoking during the study experienced improved mood regulation (for girls) and improved overall mood (for boys) as smoking increased. However, mood improvements were not observed among youth with sustained heavy use and symptoms of dependence. CONCLUSIONS: The current data argue for a model of smoking that accounts for changes in risk and maintenance factors at different points along the developmental trajectory of smoking, involving elements of both self-medication and dependence.